2007
DOI: 10.3892/ijo.30.6.1529
|View full text |Cite
|
Sign up to set email alerts
|

Honokiol, a natural biphenyl, inhibits in vitro and in vivo growth of breast cancer through induction of apoptosis and cell cycle arrest

Abstract: Abstract. Honokiol (HNK), a naturally occurring biphenyl, possesses potent antineoplastic and antiangiogenic properties. We investigated the in vitro and in vivo activity of HNK against breast cancer. HNK exhibited potent anti-proliferative activity against breast cancer cell lines and enhanced the activity of other drugs used for the treatment of breast cancer. In vivo, HNK was highly effective against breast cancer in nude mice. We identified two different effects of HNK on breast cancer cells: cell cycle in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 42 publications
1
64
0
Order By: Relevance
“…Honokiol has been found to induce apoptosis in the colon cancer cell lines RKO and to inhibit the growth of RKO cells in murine xenografts (54). We have shown that honokiol prevents the growth of MDA-MD-231 breast cancer cells in murine xenografts (59). Of interest, MDA-MD-231 cells demonstrate mutant p53 and mutant K-ras, which is preferentially observed in the triplenegative breast cancer phenotype (24,62).…”
Section: In Vivo and In Vitro Antitumor Activity Of Honokiolmentioning
confidence: 84%
“…Honokiol has been found to induce apoptosis in the colon cancer cell lines RKO and to inhibit the growth of RKO cells in murine xenografts (54). We have shown that honokiol prevents the growth of MDA-MD-231 breast cancer cells in murine xenografts (59). Of interest, MDA-MD-231 cells demonstrate mutant p53 and mutant K-ras, which is preferentially observed in the triplenegative breast cancer phenotype (24,62).…”
Section: In Vivo and In Vitro Antitumor Activity Of Honokiolmentioning
confidence: 84%
“…In addition, honokiol has a more obvious apoptosis-inducing effect on B-CLL cells than on normal mononuclear leukocytes (40). In vivo, honokiol was highly effective against SVR angiosarcoma (41) and breast cancer in nude mice (42) and in a human A549 lung cancer xenograft model (43) with the increased induction of apoptosis.…”
Section: Targeting Apoptosis Pathways In Cancer With Magnolol and Honmentioning
confidence: 89%
“…Several studies have shown that honokiol has anti-angiogenic, antiproliferative and anti-invasive activities in colon and prostate cancer cells as well as in lung, breast and ovarian cancer cells (Yang et al, 2002;Wang et al, 2004;Wolf et al, 2007;Hahm et al, 2008;Fried and Arbiser, 2009). Magnolol has also been shown to induce apoptosis and suppress the proliferation of cancer cells, and inhibit tumour metastasis in various cancer cells, including those of the colon and prostate (Lin et al, 2002;Lee et al, 2009).…”
Section: Introductionmentioning
confidence: 99%